Endoscopic Ultrasound-Guided Drainage without Fluoroscopic Guidance for Extraluminal Complicated Cysts - Hyeong Seok Nam; Hyung Wook Kim; Dae Hwan Kang; Cheol Woong Choi; Su Bum Park; Su Jin Kim; Dae Gon Ryu; Joon Ho Jeon (Gastroenterology Research and Practice)
Background. Endoscopic ultrasound- (EUS-) guided drainage is generally performed under fluoroscopic guidance. However, improvements in endoscopic and EUS techniques and experience have led to questions regarding the usefulness of fluoroscopy. This study aimed to retrospectively evaluate the safety and efficacy of EUS-guided drainage of extraluminal complicated cysts without fluoroscopic guidance. Methods. Patients who had undergone nonfluoroscopic EUS-guided drainage of extraluminal complicated cysts were enrolled. Drainage was performed via a transgastric, transduodenal, or transrectal approach. Single or double 7 Fr double pigtail stents were inserted. Results. Seventeen procedures were performed in 15 patients in peripancreatic fluid collections (n=13) and pelvic abscesses (n=4). The median lesion size was 7.1 cm (range: 2.8–13.0 cm), and the mean time spent per procedure was 26.2±9.8 minutes (range: 16–50 minutes). Endoscopic drainage was successful in 16 of 17 (94.1%) procedures. There were no complications. All patients experienced symptomatic improvement and revealed partial to complete resolution according to follow-up computed tomography findings. Two patients developed recurrent cysts that were drained during repeat procedures, with eventual complete resolution. Conclusion. EUS-guided drainage without fluoroscopic guidance is a technically feasible, safe, and effective procedure for the treatment of extraluminal complicated cysts.